Penguatan Kompetensi Guru dalam Literasi Digital di SDS IT Az-Zahra Demak - Wahyuni, Arie; Hidayati, Destia Wahyu; Kurniati, Lenny; Kusumawati, Ratih; Wulandari, Desi (Manggali, 2024)
The digital world is constantly evolving, and every individual is required to adapt quickly to technological changes. Technological changes also occur in the learning process, so that every teacher with his best performance can adapt quickly in accessing learning technology. Digitalization in learning takes various forms and functions, therefore it is necessary to strengthen teachers regarding digital literacy in learning. Digital literacy training activities at SDS IT Az Zahra Demak Demak were carried out by providing material, then continued with hands-on practice. Each service team provides assistance and guidance to all participants in practice. The results of this training activity teachers have succeeded in increasing competence which is marked by the successful practice of making assessments in Kahoot, Quiziz, and Mentimeter